Up flow plug hydrodynamic 3D-simulation into a concentric constructed tank to sludge removal - Aldana, Gerardo; Fuenmayor, José (Rev. Téc. Fac. Ing. Univ. Zulia, 2016)
Plug up flow promote hydraulic efficiency and remove organic matter through the sedimentation. To probe this affirmation a metallic tank was constructed 4 concentric rings with and different internal diameter as 3200mm, 2240mm, 1280mm and 320mm respectively. The main objective of this study was to simulate the hydrodynamic velocities vectors for the ringing tank using CFD modeling. DHI MIKE3 computer program was used. Finite Element Mesh FEM was generated and bathymetric was added varying the depth at the weir water crossing pass from 1900mm to 1700mm. Similarity condition were kept to geometric boundaries as original tank design. Methodology consist to setting up a grid with 16 sided-polygons for each ring and 3 running were done for 1440 time step of 30s each one. The simulation showed velocities vectors for the first channel ranges from 0 to 0.04 ms-1 , second ranging from 0.08 to 0.12 ms-1 and the third range from 0.04 to 0.08 ms-1 . Conclusions point out that axiallongitudinal flow was promoting and clear zones appeared with turbulence flow at reduced area such weir water crossing. First and third channel were less velocity and this match well with sediment deposits observed at the real tank.